PENERAPAN MODEL PINTAR UNTUK MENINGKATKAN BERPIKIR KRITIS DAN AKTIVITAS BELAJAR - Kristesia Elda; Ahmad Suriansyah; Ratna Purwanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aimed to improve student learning activity, critical thinking skills, and learning outcomes in Pancasila Education through the implementation of the PINTAR learning model in Year IV at SDN Teluk Dalam 12, Banjarmasin. The PINTAR model is a combination of Problem-Based Learning, Think Pair and Share, and Numbered Head Together approaches, designed to encourage active student participation. This research employed Classroom Action Research (CAR) using both qualitative descriptive and quantitative approaches. Data were collected through observation, interviews, and learning outcome tests. The findings indicate a significant improvement in teacher performance, student engagement, critical thinking abilities, and learning achievement over four meetings. This improvement aligns with the optimised learning process and continuous teacher reflection. Thus, the PINTAR model proves effective in creating a more interactive, collaborative, and meaningful learning environment, while also supporting the successful attainment of curriculum goals at the primary education level.